PENGARUH MOTIVASI KERJA, DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN HOTEL GRAND SAE DI SURAKARTA - Tama Dhea Arianindita (STIE AUB Surakarta, 2018)
The purpose of this study is to determine the significant effect of work motivation, work discipline and work environment on employee performance at Hotel Grand Sae in Surakarta. The population that became the object in this study is all employees of Hotel Grand Sae which amounted to 45 people. Samples taken at Hotel Grand Sae employees as many as 45 people. Analytical techniques in this study consisted of instrument testing, classical assumption test, multiple linear regression analysis, t test, f test and R2 test. The results of this study proves regression results on the regression equation that the work motivation and work discipline positively affect the employee performance at Hotel Grand Sae in Surakarta and the work environment negative affect the employee performance at Hotel Grand Sae in Surakarta. The result of t test shows that work motivation and work discipline have positive effect and significant influence on employee performance at Hotel Grand in Surakarta and the work environment has negative effect and not significant influence on employee performance at Hotel Grand Sae in Surakarta. The result of F test shows that there is significant influence on work motivation variable, work discipline, and work environment to employee performance at Hotel Grand Sae. Result of test of R2 (coefficient of determination) known that work motivation, work discipline and work environment can explain equal to 36,6% to employee performance of Grand Sae Hotel, while the rest equal to 63,4% explained by other variable like a work stress, leadership, organizational culture and etc.Keywords: Work Motivation, Work Discipline, Work Enviroment.